American Cold War Policies and the Enewetakese: Community Displacement, Environmental Degradation, and Indigenous Resistance in the Marshall Islands - Smith-Norris, Martha (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2011)
During the Cold War, the United States conducted 43 nuclear shots, 12 chemical explosions, and numerous missile tests on the Enewetak Atoll of the Marshall Islands. Based mainly on archival documents and congressional hearings, this case study focuses on the human and environmental consequences of these American policies. To begin with, the essay highlights U.S. interests and authority in the Marshalls. As the United Nations trustee of the region, the United States conducted these military experiments with a great deal of secrecy and little interference from the outside world. Secondly, the essay examines the significance of these tests for the Enewetakese and their removal to Ujelang, a nearby atoll, for more than three decades. Thirdly, the paper emphasizes the various forms of resistance practised by the Enewetakese. By utilizing a number of political and legal methods, this tiny indigenous community drew attention to their plight in Washington and the United Nations. Finally, the essay discusses the islanders’ attempts to gain compensation from the U.S. Congress for the profound damages caused by the testing program. To date, Washington has failed to provide enough funds to adequately restore the environment of Enewetak or to fully compensate the islanders for their losses.